DAMPAK HILIRISASI PADA INDUSTRI HALAL DI INDONESIA - Arti, Siti Wiana; Zakiyuddin , Ahmad Salim; Ridwan, Fazar Abid; Setiyawati, Lisa; Latifah, Eny (JIAR : Journal Of International Accounting Research, 2023)
Halal industry is seen as a source of economic growth engine for the country. Moreover, Indonesia, as the country with the largest Muslim population in the world, has huge potential to grow halal industries. The purpose of this research is to find out the impact of downstream on the halal industry in Indonesia. The type of research used in this study is descriptive with data trigulation techniques based on rivew litelature (perpustakaan). The results of this study show that the impact of downstream on Indonesian halal industries has constraints from various aspects, including economic, social, and environmental.